Effect of retention in elementary grades on grade 9 motivation for educational attainment. Issue 1 (February 2015) - Cham, Heining; Hughes, Jan N.; West, Stephen G.; Im, Myung Hee
Abstract This study investigated the effect of grade retention in elementary school on students' motivation for educational attainment in grade 9. We equated retained and promoted students on 67 covariates assessed in grade 1 through propensity score weighting. Retained students (31.55%, nretained = 177) and continuously promoted students (68.45%, npromoted = 384) were compared on the bifactor model of motivation for educational attainment (Cham, Hughes, West & Im, 2014). This model consists of a General factor (student's overall motivation for educational attainment), and three specific factors: student perceived Teacher Educational Expectations, Peer Educational Aspirations, and Value of Education. Measurement invariance between retained and promoted groups was established. Retained students scored significantly higher than promoted students on each specific factor but not on the General factor. Results showed that the retained and promoted students did not significantly differ on the General factor. The retained students had significantly higher scores on each specific factor than those of the promoted students. The results suggested that grade retention may not have the negative effects so widely assumed in the published literature; it is an expensive intervention with minimal evidence of benefits to the retained student.